15 years of the Journal of Intellectual Capital and counting: A manifesto for transformational IC research. Issue 1 (7th January 2014) - Dumay, John
Abstract : Purpose: – The purpose of this paper is to review and critique the current status of intellectual capital (IC) research as published in the Journal of Intellectual Capital ( JIC ) as it heads into its 15th year with a view to understanding the past and possible direction of future IC research. Design/methodology/approach: – Articles published in the JIC are reviewed building on prior IC research and analysis by Guthrie et al. (2012) and Dumay and Garanina (2013). To help understand the impact of articles in the JIC the analysis is supplemented by including citation data from google scholar, journal impact data from the SCImago Journal & Country Rank portal, and the 2013 Australian Business Dean's Council (ABDC) journal ranking list. Also included is commentary from the JIC 's senior editors based on their responses to questions asked via e-mail relating to their involvement in, and the future of, the JIC . Findings: – The JIC faces a challenge as it is most recognised as an accounting journal despite its focus on managing IC. The research published in the JIC is multidisciplinary as it comes from a wide range of perspectives. However, there appears to be a paucity of research emanating from different perspectives, most notably from North American academics, and a lack of focus on the private and public sectors. However, new perspectives of IC, especially that associated with IC praxis and the third stage of IC research are emerging as transformational opportunities for future IC research, along with the opportunity to experiment with transdisciplinary research. Originality/value: – The paper presents a comprehensive critical review of the articles published in the JIC along with measuring the impact of the articles using citation data from google scholar. Using this approach, the type of research and its impacts can be simultaneously assessed to offer insights into future transformational IC research opportunities, and how IC researchers and the JIC can also be transformational.